The usage of social media in weight management among undergraduate nursing students - Daud, Azlina; Othman, Hamidah; Masran, Nur Hasyimah; Pairoh, Hasanah (ACADEMIC INSPIRED NETWORK, 2023)
Social media platforms have become an integral part of the lives of many young adults, and they can have both positive and negative effects on weight management. They tend to utilize their smartphones to check on social media and find information through the internet in their lives. This convenience makes it a go-to device for quick information to seek information related to physical exercise and diet practice for weight management. Physical exercise and diet are two crucial components of weight management. This study aimed to assess the association between the usage of social media and weight management among undergraduate students. This study aimed to assess the association between usage of social media and physical activities and dietary practice. A cross-sectional sectional study was conducted among 191 undergraduate nursing students. A convenient sampling method was used. The participants answer the online questionnaire that sent via WhatsApp link to self-reported Google forms. The questionnaire consists of socio-demographic parts, a social media usage questionnaire, a dietary practice questionnaire, and IPAQ-SF. The results showed that there is an association between the frequency of posting on social media and physical activity with a p-value <0.05. The frequency of time spent on social media daily is associated with dietary practices among the participants (p<0.05). This study also revealed that WhatsApp and Instagram are the most popular social media sites among the participants. This study underscores the frequency of time spent on social media daily is associated with dietary practices among undergraduate students where they have a high possibility to engage more with any post related to dietary practice information.